(untitled) (Bangladesh Critical Care Journal, 2026)
Pituitary adenomas commonly present with visual or hormonal disturbances, while vascular complications are rare and usually associated with pituitary apoplexy. We describe a 70-year-old man who presented with acute right upper limb weakness and dysarthria consistent with a transient ischemic attack. Magnetic resonance imaging (MRI) revealed a giant pituitary macroadenoma with bilateral parasellar extension, more pronounced on the right side, with encasement of the right cavernous carotid artery, giving it the appearance of the “snowman sign”. Bangladesh Crit Care J March 2026; 14 (1): 65-67